Biloma secondary to blunt liver trauma in a pediatric patient: case report - Sánchez, Omar Sosa; Tovar, Fernando Navarro; Montaño , Mónica Heredia; Barrientos, Cheryl Zilahy Diaz; Ponce, Mildred Philipe; Pérez, Yoselin Julisa Sarabia (International Journal of Research in Medical Sciences, 2023)
Liver is the organ most frequently injured after blunt or penetrating abdominal trauma, being in pediatrics a pathology that has an increasing incidence; Non-operative management is the hallmark of treatment, however cases of secondary biliary leakage have been described, which may affect the intrahepatic or extrahepatic track. A male 8 years old, with blunt trauma in the right hypochondrium, presenting acute abdomen and hemodynamic instability, requiring exploratory laparotomy with a grade III liver injury in VI and VII hepatic segments. Four weeks after discharge, he presented as a complication a giant biloma in VII and VIII hepatic segments, performing percutaneous drainage guided by ultrasound. The incidence of biliary complications related to hepatic trauma is low, 4% in pediatric patients, dividing into bilomas or biliary fistulas; the presentation of biliary leakage is very non-specific and early diagnosis difficult; in the bilomas, the tomography allows to define precisely its size, nature, distribution and regional anatomy in relation to adjacent structures, as well as underlying cause. The approach of choice is percutaneous or endoscopic drainage, with surgical management being the last option.